2020
DOI: 10.3390/jcm9072152
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Reverse Remodeling of the Native Cardiac Conduction System after Cardiac Resynchronization Therapy

Abstract: Background: Little is known about electrical remodeling of the native conduction systems, particularly how the PR interval changes, after cardiac resynchronization therapy (CRT). We investigated the effects of CRT on the intrinsic PR interval (i-PRi) and QRS duration (i-QRSd). Methods and results: In 100 consecutive CRT recipients with sinus rhythm and long-term follow-up (>1 year), the i-PRi and i-QRSd were measured at baseline and at the last echocardiographic follow-up (33.4 ± 17.9 months) with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…In addition to QRS narrowing, we found shorter baseline pre-CRT intrinsic PR interval to be significantly associated with favorable post-CRT outcomes. Previous studies [ 20 , 21 , 22 ] have pointed to a possible correlation between shorter baseline PR interval and better prognosis following CRT implantation. Interestingly, in contrast with QRS narrowing characterizing CRT responders, post-CRT PR interval tends to prolong, regardless of CRT response [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to QRS narrowing, we found shorter baseline pre-CRT intrinsic PR interval to be significantly associated with favorable post-CRT outcomes. Previous studies [ 20 , 21 , 22 ] have pointed to a possible correlation between shorter baseline PR interval and better prognosis following CRT implantation. Interestingly, in contrast with QRS narrowing characterizing CRT responders, post-CRT PR interval tends to prolong, regardless of CRT response [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 20 , 21 , 22 ] have pointed to a possible correlation between shorter baseline PR interval and better prognosis following CRT implantation. Interestingly, in contrast with QRS narrowing characterizing CRT responders, post-CRT PR interval tends to prolong, regardless of CRT response [ 22 ]. Further research is thus needed to examine the prognostic effects of monitoring post-implantation changes in intrinsic PR interval.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, after a mean follow-up of 59 ± 26 months, there was an increase in the number of patients treated and the dosage administered in the majority of patients. The variability of AV conduction was documented in both ways: shorter PR interval during physical exercise due to increased heart rate and the subsequent need to program rate-adaptive AV interval and increased intrinsic PR interval after resynchronization, irrespective of the CRT response status [27,28]. In the current study group, the main reasons for avoiding high BB doses were a longer baseline PR interval or a documented prolonged AV conduction during ET.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, we compared extent of iQRS duration change in patients with mechanical response versus without mechanical response. Data were extracted from six studies with 356 participants, of whom 231 (64.9%) were defined as mechanical responders [14,19,[21][22][23][24]. We found that while mechanical responders had a mean of iQRS shortening of 7.7 ms, mechanical non-responders experienced widening of iQRS by mean of 5.2 ms (Supplementary Fig.…”
Section: Association Between Electrical and Mechanical Responsementioning
confidence: 99%